Cerebral compensation during motor function in Friedreich ataxia: The IMAGE‐FRDA study. Issue 8 (27th May 2017) - Harding, Ian H.; Corben, Louise A.; Delatycki, Martin B.; Stagnitti, Monique R.; Storey, Elsdon; Egan, Gary F.; Georgiou‐Karistianis, Nellie
ABSTRACT: Background : Friedreich ataxia is characterized by progressive motor incoordination that is linked to peripheral, spinal, and cerebellar neuropathology. Cerebral abnormalities are also reported in Friedreich ataxia, but their role in disease expression remains unclear. Methods : In this cross‐sectional functional magnetic resonance imaging study, 25 individuals with Friedreich ataxia and 33 healthy controls performed simple (self‐paced single‐finger) and complex (visually cued multifinger) tapping tasks to respectively gauge basic and attentionally demanding motor behavior. For each task, whole brain functional activations were compared between groups and correlated with disease severity and offline measures of motor dexterity. Results : During simple finger tapping, cerebral hyperactivation in individuals with Friedreich ataxia at the lower end of clinical severity and cerebral hypoactivation in those more severely affected was observed in premotor/ventral attention brain regions, including the supplementary motor area and anterior insula. Greater activation in this network correlated with greater offline finger tapping precision. Complex, attentionally demanding finger tapping was also associated with cerebral hyperactivation, but in this case within dorsolateral prefrontal regions of the executive control network and superior parietal regions of the dorsal attention system. Greater offline motor precision was associated with less activation in the dorsal attention network. Discussion : Compensatory activity is evident in the cerebral cortex in individuals with Friedreich ataxia. Early compensation followed by later decline in premotor/ventral attention systems demonstrates capacity‐limited neural reserve, while the additional engagement of higher order brain networks is indicative of compensatory task strategies. Network‐level changes in cerebral brain function thus potentially serve to mitigate the impact of motor impairments in Friedreich ataxia. © 2017 International Parkinson and Movement Disorder Society